Epigenetic dysregulation of the IGF system in placenta of newborns exposed to maternal impaired glucose tolerance. (April 2014) - Desgagné, Véronique; Hivert, Marie-France; St-Pierre, Julie; Guay, Simon-Pierre; Baillargeon, Jean-Patrice; Perron, Patrice; Gaudet, Daniel; Brisson, Diane; Bouchard, Luigi
Aims: To determine whether placental IGF1R, IGFBP3, INSR and IGF1 DNA methylation and mRNA levels were dysregulated when exposed to maternal impaired glucose tolerance (IGT) and investigate whether the epigenetic profile is associated with feto-placental developmental markers.Patients & methods: The IGT diagnosis was made according to the WHO criteria (IGT: n = 34; normal glucose tolerance [NGT]: n = 106). DNA methylation and mRNA levels were quantified using bisulfite pyrosequencing and qRT-PCR, respectively.Results: IGF1R and IGFBP3 DNA methylation levels were lower in placentas exposed to IGT compared with NGT (-4.3%; p = 0.021 and -2.5%; p = 0.006 respectively) and correlated with 2-h post-oral glucose tolerance test (OGTT) glycemia (r = -0.23; p = 0.010 and r = -0.20; p = 0.028, respectively). IGF1R mRNA levels were associated with newborns' growth markers (e.g., birth weight; r = 0.20; p = 0.032).Conclusion: These results support the growth-promoting role of the IGF system in placental/fetal development and suggest that the IGF1R and IGFBP3 DNA methylation profiles are dysregulated in IGT, potentially affecting the fetal metabolic programming.